ANGER AS A MEDIATOR OF THE EFFECTS OF ANXIETY ON AGGRESSIVENESS IN TEACHER TRAINEES - Cankaya, Ibrahim (Soc Personality Res Inc, 2011)
In this study the aim was to assess the effects of anxiety on aggressiveness as mediated by anger in teacher trainees. The study group was composed of senior-year students attending Firat University in Turkey during the fall semester of the 2009-2010 academic year. Data from 251 students were analyzed using LISREL version 8.51. It was found that the direct effect of anxiety on aggressiveness was reduced when mediated through anger. Among trainee teachers, anxiety was found to affect aggressiveness in a more positive direction through anger.
Keywords: anxiety; aggressiveness; anger; trainee teachers